Power Optimization of a Three-Node Two-Way Relay-Assisted Power-Line Communication System - Liong, Ann Gie; Gopal, Lenin; Rong, Yue; Juwono, Filbert; Chiong, Choo W. R. (2022)
Two-way communication links are required in power-line communication (PLC) as a smart grid enabler. As PLC systems suffer from harsh power-line channels, it is beneficial to provide spatial diversity to improve the system performance. Using a two-way multicarrier relay configuration, this paper investigates the power optimization of a relay-assisted PLC system with the consideration of the quality of service (QoS) constraints. Since the QoS constrained power allocation problem is highly non-convex, an alternating optimization (AO) algorithm is proposed to decompose the optimization problem into subproblems. Simulation results show the proposed system is able to reduce the total power required by the system for about 40% compared to the conventional bidirectional direct transmission (BDT) system under the same QoS requirement. Further, the proposed system consumes less power compared to the relayassisted two-way information exchange (R2WX) system.